Progressive Pedagogies and Teacher Education: A Review of the Literature - Webber, Geoff; Miller, Dianne (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
Few studies take up the question of how to teach pre-service or current teachers to practice integrated, interdisciplinary, and inquiry-based methodologies. In this literature review, scholarly research is explored to examine approaches to teacher education based in progressivism. Place- and community-based education is considered as an important approach for heightened student engagement in relation to social justice, rural revitalization, and Indigenous knowledges. Characteristics of strong teacher education programs are also examined. This broad investigation lays the foundation for a deeper inquiry into the organization and development of teacher education programs. Conclusions point to recommendations for teacher education programs with recognition of the potential for critical place-based education within the field of teacher education.